Chapter Didattica con i testimoni, l'esperienza con Silvano Sarti - Vitulano, Massimo (Public History of Education. Teorie, esperienze, strumenti, 2022)
The paper aims at dealing with didactics of Resistance through the relationship between the historical wtnesses and younger generations. As the first has lived the historical events he is going to narrate, younger generations constitute ideally the depositary of a rich and fragile set of informations. Based from this perspective, the paper is going to speak about a students' cycle of meetings organised in some schools in the province of Pistoia, between 2016 and 2018: the vocational institute "Martini" and the technical institute "Marchi". Meetings were held by SIlvano Sarti, who fought as partisan in the "Brigata Sinigaglia" in 1944 and who was appointed ANPI provincial president in Florence.